THE READING COMPREHENSION PROBLEMS FACED BY ENGLISH DEPARTMENT STUDENTS OF SYIAH KUALA UNIVERSITY - Merina Devira Devira (Program Studi Pendidikan Sejarah - Universitas Samudra, 2017)
Reading comprehension is the process of understanding the meaning of written language by reconstructing the author’s message using one’s experiential knowledge, knowledge of language, and thinking skills. The students’ reading comprehension problems can be solved by mastering reading comprehension skills. The objectives of this study are to find out in which reading comprehension skills the English Department students have difficulties and what factors affecting them. The method used in this study was a descriptive qualitative method. The sample of this research was 30 English Department students of Syiah Kuala University who have passed Reading Comprehension IV at least with a C grade. The data was collected by using a test and an interview. The questions on the test were designed based on 13 reading comprehension skils. The research results show that English Department students have difficulties in mastering reading comprehension skills. The major difficulties faced by them are difficulty in answering transition questions (80.75%), implied detail questions (61.20%), unstated detail questions (61%), and vocabulary questions (56%). In addition, the students’ lack of reading comprehension skill were affected by some factors including the background knowledge, the difficulty of material, the purpose of reading, concentration, motivation, and reading interest. Based on the research results, the writer recommends that the students do more reading comprehension practice by implementing some reading comprehension skills and extensively read a lot of English reading materials.